2015
DOI: 10.1097/sla.0000000000001401
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome After Laparoscopic Ventral Mesh Rectopexy

Abstract: LVR is safe and effective for the treatment of different rectal prolapse syndromes. Long-term recurrence rates are in line with classic types of mesh rectopexy and occurrence of mesh-related complications is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
2
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(73 citation statements)
references
References 40 publications
2
57
2
12
Order By: Relevance
“…Thirty-eight of those 46 studies were excluded due surgery other than ventral rectopexy having been performed, postoperative complications not having been reported, or mesh-related erosion having not been observed among the complications; thus, eight studies were deemed eligible for inclusion (Fig. 1) [1213141516171819]. All studies reported synthetic mesh-related erosion [1213141516171819], and 1 study [19] reported both synthetic and biological mesh-related erosion (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-eight of those 46 studies were excluded due surgery other than ventral rectopexy having been performed, postoperative complications not having been reported, or mesh-related erosion having not been observed among the complications; thus, eight studies were deemed eligible for inclusion (Fig. 1) [1213141516171819]. All studies reported synthetic mesh-related erosion [1213141516171819], and 1 study [19] reported both synthetic and biological mesh-related erosion (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…1) [1213141516171819]. All studies reported synthetic mesh-related erosion [1213141516171819], and 1 study [19] reported both synthetic and biological mesh-related erosion (Table 1). Six studies were prospective, none of which was a randomized clinical trial [121314151619], 1 study was retrospective [17], and 1 study was a case report (Table 1) [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the primary objective of this study was to test the hypothesis that RPR rates are higher in women with clinically significant POP relative to women without POP. Given the notion that RPR might be greater after perineal vs abdominal repairs, as suggested by existing literature, 2,1620 we also aimed to assess the combined effect of POP and surgical route on outcomes of RP repair.…”
mentioning
confidence: 99%